It's not about adjustment costs: Estimating asymmetries in long-run labor demand using a fractional panel probit model - Arnd Kölling (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2018)
Models of labor demand usually use cost or production functions to derive profit maximizing firm performance. These models often rely on the assumption of symmetric behavior, that is, the response to a positive or negative wage shock of the same relative size is identical to the shock, and the estimated labor demand elasticities are the same for increasing and decreasing employment. However, models like loss aversion and endowment effects question the assumption of symmetry in labor demand. In addition, the influence of a labor shortage should be reflected in the investigations. Estimations of Fractional Panel Probit models for three different skill levels are applied to evaluate these findings with a large panel of German establishments. The results indicate asymmetric structures for long-run own-wage elasticities and for some cross-wage elasticities, putting some doubt on the assumption of strict rationality in labor demand and indicating the influence of labor shortages. – – Modelle der Arbeitsnachfrage leiten das optimale Verhalten von Unternehmen häufig aus Kostenbzw. Produktionsfunktionen ab. Die Analysen basieren häufig auf der Annahme eines symmetrischen Verhaltens bei Einstellungen oder Entlassungen, d.h. identische relative Lohnerhöhungen oder - senkungen führen zu denselben positiven bzw. negativen Beschäftigungseffekten in absoluter Höhe. Modelle der Verhaltensökonomik wie z.B. Verlustaversion und "Endowment-Effekte" stellen jedoch die Annahme der Symmetrie in Frage. Außerdem wird der mögliche Einfluss eines Fachkräftemangels auf symmetrische Veränderungen untersucht. Die Nachfrage nach drei Qualifikationsstufen wird mit Hilfe eines "Fractional Panel Probit"-Ansatzes geschätzt. Dazu wird ein großer Paneldatensatz auf Betriebsebene herangezogen. Die Ergebnisse deuten auf asymmetrische Lohnelastizitäten hin. Dies zeigt einerseits den Einfluss des Fachkräftemangels, weckt aber auch andererseits Zweifel an der Annahme von rational handelnden Betrieben.
Keywords: 330